Intravenous ferric carboxymaltose for iron deficiency anemia in dialysis patients: Effect of a new protocol adopted for a hemodialysis limited assistance center. Issue 6 (20th March 2020) - Gobbi, Laura; Scaparrotta, Giuseppe; Rigato, Matteo; Cattarin, Leda; Qassim, Laila; Carraro, Gianni; Rossi, Barbara; Calò, Lorenzo A.
Abstract: Iron and erythropoietin deficiencies are determinants of anemia in chronic kidney disease. In hemodialysis (HD) patients, intravenous (IV) iron is associated with a greater hemoglobin (Hb) production and better erythropoietin response but may be associated to hypersensitivity reaction. After the 2013 European Medicines Agency report regarding early detection/management of iron allergic reactions, IV iron administration dramatically reduced in Italian Hemodialysis‐Limited‐Assistance‐Centre (HD‐CAL) where a physician is present only once a week. Objective of the study was providing an effective and secure IV iron administration protocol for HD‐CAL patients. IV ferric carboxymaltose (FCM) administration was more effective and better tolerated than sodium ferric gluconate for iron deficiency correction and resolution of anemia in 24 patients undergoing HD in our HD‐CAL. Six months of FCM IV treatment once a week increased ferritin and Hb compared to sodium ferric gluconate once a week leading to decreased erythropoietin consumption from 24 000 to 15 000 U/patient/week with an erythropoietin annual expense reduction. No blood transfusions, gastrointestinal intolerance or other adverse effects were reported. The FCM IV administration protocol for our HD‐CAL patients was safe and no adverse events were reported, resulting in significantly increased ferritin, transferrin saturation, and Hb levels, reduction of erythropoietin requirements, and consequently reduction of erythropoietin expenses.